Accessing Coverage Barriers and Impact of Socio-Cultural Factors on Tetanus Toxoid Immunization Uptake among Women of Child Bearing Age in Ogun State Nigeria (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction: tetanus toxoid is a vaccine preventable disease that is caused by a life-threatening bacterial infection called clostridium tetani. the vaccine is usually given to women of reproductive age in order to protect both mother and newborn from maternal and neonatal tetanus. this study aims to access the coverage barriers and impact of socio-cultural factors on the uptake of the tetanus toxoid immunization in other to reduce the burden of the disease as a public health concern. Methods: This study utilized a mixed-methods approach. A semi-structured questionnaire was administered to women of childbearing age. One Local Government Area (LGA) was randomly selected from each senatorial district in Ogun State, Nigeria, using a sampling frame. Data were collected, cleaned in Microsoft Excel, and analyzed using SPSS version 27.Results: The coverage level of uptake of the Tetanus Toxoid immunization is 78.7%based on the result of the study. However, the dosage breakdown further clarifies the immunization dosage received, while 381(37.6%) women received one dose, 261 (25.8%) women received two doses of the tetanus toxoid vaccine, while 15.3% (155) received three doses which indicate a need for increased awareness about the recommended immunization schedule. these figures collectively show the coverage level of tetanus toxoid vaccine. Cultural or religious beliefs affect women’s decisions to receive tetanus toxoid immunization with 198 rural women stated that these beliefs influenced their decisions, while 267 said they did not. In urban areas, 164 women reported that cultural or religious beliefs affected their decision-making, while 299 said they were not influenced by such factors. The Chi-square value of 5.951 and P-value of 0.051 indicate a narrow significant difference.Conclusion: This study explored coverage barriers and impact of socio-cultural factors on tetanus toxoid immunization uptake. The findings spread across significant associations between socio-demographic variables, healthcare accessibility, cultural beliefs and immunization coverage. The results show a very good indicator of uptake of preventive care vaccine, the cultural and Religious Beliefs shows their attitude towards the immunization decisions, a reasonable amount of women in rural areas said such belief hinder their decision to receive the vaccine.